The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1016/j.cnsns.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous formation of bright solitons in self-localized impurities in Bose–Einstein condensates

Abstract: We study the formation of bright solitons in the impurity component of Bose-Einstein condensateimpurity mixture by using the time-dependent Hartree-Fock-Bogoliubov theory. While we assume the boson-boson and impurity-boson interactions to be effectively repulsive, their character can be changed spontaneously from repulsive to attractive in the presence of strong anomalous correlations. In such a regime the impurity component becomes a system of effectively attractive atoms leading automatically to the generati… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…The anomalous density could play a key role in understanding the superfluidity of liquid droplets since both quantities arise from atomic correlations [53,56]. At large anomalous correlations (pairing instability), one can expect that the self-bound BEC may split into several peaks which remain spatially localized [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…The anomalous density could play a key role in understanding the superfluidity of liquid droplets since both quantities arise from atomic correlations [53,56]. At large anomalous correlations (pairing instability), one can expect that the self-bound BEC may split into several peaks which remain spatially localized [57,58].…”
Section: Discussionmentioning
confidence: 99%
“…In such a case, a diffraction pattern at early time-evolution is observed signaling the relevance of quantum effects. Note that similar behavior holds in bright solitons in a pure BEC [35] and in Bose polarons [36] where the soliton splits into two partially coherent solitonic structures owing to the effects of quantum fluctuations. At finite temperatures, one can expect that the two splitting droplets each being a mixture of bounded and unbounded atoms.…”
Section: Periodic Modulationmentioning
confidence: 58%
“…The inclusion of the anomalous correlations in a 3D harmonically trapped Bose gas, accounts well for shifts in the lower-lying excitation of the JILA experiment [27,33]. In attractively interacting BECs, it has been found that the anomalous fluctuation causes the condensate to collapse and the 1D soliton to split into two solitonic structures [31,32,35,36].…”
Section: Introductionmentioning
confidence: 99%
“…The TDHFB equations which we choose to employ here constitute a model well suited to this task because it governs both the dynamics of the condensate and the anomalous density at finite temperature. In this quasi-1D geometry, the TDHFB equations may be represented as [21,23,29,30,[34][35][36][37][38]:…”
Section: Tdhfb Formalismmentioning
confidence: 99%
See 1 more Smart Citation